Se-mediated dry transfer of wafer-scale 2D semiconductors for advanced electronics - Xingchao Zhang; Lanying Zhou; Shuopei Wang; Tong Li; Hongyue Du; Yuchao Zhou; Jieying Liu; Jiaojiao Zhao; Liangfeng Huang; Hua Yu; Peng Chen; Na Li; et al. (Nature Communications)
Abstract Two-dimensional (2D) semiconductors hold a great promise for next-generation electronics. Yet, achieving a clean and intact transfer of 2D films on device-compatible substrates remains a critical challenge. Here, we report an approach that uses selenium (Se) as the intermediate layer to facilitate the transfer of wafer-scale molybdenum disulfide (MoS2) monolayers on target substrates with high surface/interface cleanness and structural integrity. Our method enables nearly 100% film intactness of the transferred 2D semiconductors which are free from residues or contaminants. Characterizations reveal that the Se-assisted dry-transfer yields MoS2 film with superior quality compared to conventional transfer techniques. The fabricated field-effect transistors (FETs) and logic circuits based on these transferred films demonstrate remarkable electrical performance, including on/off current ratios up to 2.7×1010 and electron mobility of 71.3 cm2·V-1·s-1 for individual FETs. Our results underscore the feasibility of this dry-transfer technology for fabricating high-performance 2D electronics that are fully compatible with standard semiconductor processes, paving the way for integrating 2D materials into advanced electronic applications.